Answer:
x = 13°
Step-by-step explanation:
m<EGF + m< FGH = m<EGH
or, 3x+6+5x-7 = 103°
or, 8x-1 = 103°
or, 8x = 103°+1°
or, x = 104°/8
or, x = 13°
Now,
m<EGF = 3x+6
= 3×13+6
= 39+6
= 45
m<FGH = 5x-7
= 5×13-7
= 65-7
= 58
Answer:
No
Step-by-step explanation:
Direct variation: two variables, one variable is a constant multiple of another variable
y = k x .... k constant
-x+4y=-2
4y = x - 2
y = 1/4 x -1/2 ..... y = k x + b y is not a simple multiple of x
When multiplying exponents, remember the first rule: when multiplying similar bases, add powers together. 52% + 56% =? The bases of the equation remain unchanged, while the exponents' values are added together. Adding the exponents is only a quick way to get at the answer. Simply add the exponents to multiply exponential expressions with the same base. Simplify. The product rule applies because the base of both exponents is a. With a common basis, add the exponents.
Answer:
A, B, C
Step-by-step explanation:
whole number: the set of counting numbers, 1, 2, 3, ..., and includes the number 0.
integer: all whole numbers, zero, and all the negatives of the whole numbers: ..., -3, -2, -1, 0, 1, 2, 3, ...
rational: any number that can be written as a fraction of integers
irrational number: a number that cannot be written as a fraction of integers
1.00 is the same as 1
It is:
A whole number
B integer
C rational
Answer: ∠EDC or ∠CDE
Step-by-step explanation: